PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA GURU SD - Hermawan, Desky Yanif; Miyono, Noor; Abdullah, Ghufron (Universitas Muria Kudus, 2022)
This study aims to determine the contribution of organizational culture to the performance of elementary school teachers in the Regional Coordinator for Education, Jambu District, Semarang Regency. Data collection using instruments. Data processing using normality test and simple regression test. The results of the teacher's performance normality test showed the Asymp value. Sig. (2-tailed) 0.092 and organizational culture shows the value of Asymp. Sig. (2-tailed) 0.089. The value is greater than = 0.05. Thus it can be concluded that the data on organizational culture variables are normally distributed. The results of the regression test show that there is a significant influence of organizational culture on performance which is stated in the equation = 54.538 + 0.353 X1 with a correlation strength of 0.267 with a contribution of 0.072 = 7.2%, meaning that the influence of organizational culture on teacher performance is 7.2% and the remaining 92 ,8% influenced by other factors